Thermoplastic polyurethane/(organically modified montmorillonite) nanocomposites produced by in situ polymerization - M. Strankowski; J. Strankowska; M. Gazda; L. Piszczyk; G. Nowaczyk; S. Jurga (eXPRESS Polymer Letters)
A series of polyurethane nanocomposites were synthesized from thermoplastic polyurethanes (with different hard segment ratios) and two types of organically modified montmorillonites (OMMT) – Cloisite® 10A and Cloisite® 20A. The thermal behavior was examined by non-isothermal thermogravimetry (TG, DTG), Differential Scanning Calorimetry (DSC) and Dynamic-Mechanical Thermal Analysis (DMTA). The results of X-ray analyses showed that the OMMT produced the intercalated polyurethane nanocomposites. It has been proven that the thermal stability and tensile properties of these new systems were higher when the organoclay was present within the polymer matrix. Moreover, these properties depend on both the OMMT loading and the type of gallery cations of the organically modified montmorillonites.